ERK-ERF-EGR1, a novel switch underlying acquisition of a motile phenotype - Ben-Chetrit, Nir (Landes Bioscience, 2013)
Unlike the well-characterized checkpoints of the cell cycle, which establish commitment to cell division, signaling pathways and gene expression programs that commit cells to migration are incompletely understood. Apparently, several molecular switches are activated in response to an extracellular cue, such as the epidermal growth factor (EGF), and they simultaneously confer distinct features of an integrated motile phenotype. Here we review such early (transcription-independent) and late switches, in light of a novel ERK-ERF-EGR1 switch we recently reported in the FASEB Journal. The study employed human mammary cells and two stimuli: EGF, which induced mammary cell migration, and serum factors, which stimulated cell growth. By contrasting the underlying pathways we unveiled a cascade that allows the active form of the ERK mitogen-activated protein kinase (MAPK) cascade to export the ERF repressor from the nucleus, thereby permitting tightly balanced stimulation of an EGR1-centered gene expression program.